Study of hysterosalpingography and fallopian tube recanalization in evaluation and treatment of infertile female in tertiary care center: prospective observational study - Zarariya, Ashish; Lanjewar, Kajal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Infertility affects about 10-15% of couples, with tubal factors contributing to nearly one-third of female infertility cases. HSG remains the first-line imaging modality for evaluating uterine and tubal pathology, while FTR provides a minimally invasive treatment for proximal tubal block. Methods: This prospective cross-sectional observational study was conducted in the department of obstetrics and gynecology, Government Medical College, Nagpur, over 18 months (January 2023-June 2024). Sixty infertile women meeting inclusion criteria were evaluated using HSG. Cases with proximal tubal block were selected for FTR. Data were analyzed using SPSS version 21, with p<0.05 considered statistically significant. Results: The mean age of participants was 29.03±4.17 years, and the mean duration of infertility was 4.66±3.79 years. HSG showed normal findings in 58.3% and abnormal findings in 41.7% of patients, with bilateral cornual block being the most frequent abnormality. FTR was performed in 8 patients, with successful tubal patency achieved in 5 (62.5%) and conception in 3 (37.5%). There was no significant association between HSG findings and conception rate (p>0.05). Conclusions: HSG is a simple, reliable, and cost-effective method for initial evaluation of tubal patency. FTR is a safe and effective therapeutic procedure for managing proximal tubal obstruction, improving fertility outcomes, and reducing the need for more invasive interventions.